Bed Diplomacy - Omona, David Andrew (My University, 2021)
Bed diplomacy is an informal kind of diplomacy where peaceful relationship between two or more parties is hatched, enacted, cemented, maintained, and reenacted through marriage. This form of establishing, maintaining, and reenacting relationships between people of diverse traditions has been part of human interaction from antiquity. Whereas right from antiquity women were blamed for all ills of life, as seen in the writings of the Greek Hesiod in the myth of the great woman “Pandora” – who is believed to have “opened the lid of a jar containing all plagues and diseases of the world and let them out” (Pomeroy et al. 2004, p. 72), they also have invariably been the source of enacting, maintaining, and reenacting peaceful relationships between people who are or would have been enemies
Keywords: Bed · Conflict · Diplomacy